Pembuatan Bioetanol Dari Air Limbah Cucian Beras Menggunakan Metode Hidrolisis Enzimatik Dan Fermentasi - Eva Fadillah (JURAL RISET RUMPUN ILMU TEKNIK, 2022)
This study aims to utilize rice washing wastewater as a potential raw material for bioethanol production using enzymatic hydrolysis and fermentation methods. The wastewater is treated with amylase enzyme to break down starch into simple sugars, which are then fermented using yeast to produce ethanol. The research involves optimizing process conditions such as temperature, pH, enzyme concentration, and fermentation time. The results indicate that rice washing wastewater has the potential to be an efficient raw material for bioethanol production. Thus, this study contributes to the development of renewable energy sources and the utilization of agricultural waste to create a more sustainable economic cycle.